Infisdial as Learning Media for Strengthening "Anti Bullying" Attitudes - Rahma, Zuyyina; Winarno; Al Rasyid, Machmud (Journal of Education Technology, 2023)
Bullying is increasingly common in Indonesia, especially in school environments. Teachers have a very important contribution to overcoming bullying behavior towards students, one of which is by providing interesting but still effective learning to transform knowledge and information as well as life values through learning at school. The learning process can be carried out using learning media. The aim of this research is to develop infographic-based learning media through social media that can strengthen students' anti-bullying attitudes. This development uses the ADDIE model. This study involving material experts and media experts, as well as Pancasila Education subject teachers and 30 Phase E students as research subjects. Data collection was carried out using questionnaires and interviews. At the validation stage, the material expert received the "Very good" category. The results of the Independent Sample T-test were interpreted to show that the calculated t value was greater than the t table so that it could be concluded that H0 was rejected and H1 was accepted with the test decision being that the experimental class mean was greater than the control class. This shows that treatment using informal media has a significant impact on strengthening the value of anti-bullying attitudes in students.